Factores predictores asociados al tiempo de recuperación en recién nacidos con dificultad respiratoria ingresados en una UTIN de un hospital de Loreto, julio a diciembre de 2024 - Bicerra Ribeiro, Melina del Carmen (2025)
Introduction: In neonates, respiratory failure represents a medical emergency of high severity, with the potential to trigger lethal events and compromise the initial health status. This condition can arise from multiple etiologies, including pulmonary immaturity associated with premature births, structural defects present from birth, infectious processes, or injuries sustained during delivery. Clinically, it manifests through signs such as accelerated respiratory rate, intercostal space retractions, expiratory grunting, and a bluish discoloration of the skin due to lack of oxygen. Specifically in the Loreto region, the provision of neonatal medical care is hindered by geographical remoteness and scarcity of health resources, intensifying the complexity in managing this critical condition. Objective: To determine the predictive factors with recovery time in newborns admitted with respiratory difficulty at a Hospital in Loreto, 2024. Study Population: The study population will include neonates with acute respiratory distress from the neonatal intensive care unit of the Regional Hospital of Loreto during the year 2024, with a sample size of 198 subjects. Method: The research will be analytical in nature, employing an observational, prospective, and cross-sectional design. Results: To determine the outcomes of the proposed study, data will be imported from Excel to SPSS 26.0 for statistical analysis. Descriptive statistics and inferential tests will be used to evaluate associations between dichotomous variables in small samples. Survival analyses will help identify predictive factors. A value of (P < 0.05) would indicate statistical significance with 95% confidence. Conclusions: The research aims to provide specific data on which predictive factors are most associated with longer or shorter recovery time in neonatal respiratory difficulty in Loreto, in order to improve neonatal care and contribute to global knowledge on this complication.